141k views
0 votes
What are the steps to solve 4p-3=-9+7p

1 Answer

2 votes

Answer:

p = -4

Explanation:

So first of all, you need to combine like terms. In order for that to happen, you need the like terms on one side. You get rid of a number by adding ( if subtraction), multiplying (if division), and subtracting (if addition) by its reciprical. Since it is a negative 3, you add it. Whatever you do to one side, you have to do to the other. That leaves us to 4p = 9 + 7p +3 or 4p = 12 + 7p. Since 7p is positive, you have to subtract from both side leaving us with 4p - 7p = 12 or -3p = 12. You then divide both sides with -3 to isolate the variable leaving us with p = -4

User Hardik Gajjar
by
5.5k points